2017
DOI: 10.1044/2016_jslhr-s-16-0192
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Bioenergetic Considerations for Intrinsic Laryngeal Skeletal Muscle Physiology

Abstract: Muscle bioenergetics, a key component for muscle training, detraining, and fatigue models in exercise science, is a little-considered aspect of intrinsic laryngeal skeletal muscle physiology. Partnered with knowledge of occupation-specific voice requirements, application of bioenergetics may inform novel considerations for voice habilitation and rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 32 publications
0
7
0
3
Order By: Relevance
“…In response to endurance training, aged men and women experience similar increases in maximum oxygen uptake, muscle enzyme activities, muscle bed capillarization, and muscle transformations from Type IIb to Type IIa (Coggan et al, 1992;Kohrt et al, 1991;Rogers & Evans, 1993). Type IIb muscle fibers, which are undifferentiated fibers, are currently referred to as Type IIx fibers in humans (Powers & Howley, 2014;Sandage & Smith, 2017). Overall, endurance training similarly affects the skeletal muscle properties and maximum oxygen uptake in men and women (Coggan et al, 1992).…”
Section: Hormones and Response To Exercisementioning
confidence: 99%
“…In response to endurance training, aged men and women experience similar increases in maximum oxygen uptake, muscle enzyme activities, muscle bed capillarization, and muscle transformations from Type IIb to Type IIa (Coggan et al, 1992;Kohrt et al, 1991;Rogers & Evans, 1993). Type IIb muscle fibers, which are undifferentiated fibers, are currently referred to as Type IIx fibers in humans (Powers & Howley, 2014;Sandage & Smith, 2017). Overall, endurance training similarly affects the skeletal muscle properties and maximum oxygen uptake in men and women (Coggan et al, 1992).…”
Section: Hormones and Response To Exercisementioning
confidence: 99%
“…Posteriormente, los receptores ubicados en su interior se sensibilizan y se desencadena la respuesta dolorosa (Mense, 2008). En la muestra estudiada, el 100 % de las participantes evidenciaron sentir dolor cuando los músculos aductores son sometidos a sobrecarga, siendo la de mayor frecuencia aquella que requiere de mayor gasto energético (aumento de la intensidad vocal) (Sandage & Smith, 2017).…”
Section: Discussionunclassified
“…The length of time the muscle contraction was activated was aligned with reliance on aerobic metabolism which is not typically associated with muscle hypertrophy. 3 In contrast, Karbiener et al 45 demonstrated intrinsic laryngeal muscle hypertrophy in an NMES sheep model. Their NMES protocol stimulated the recurrent laryngeal nerve for only 2 minutes each day for an overall duration of 29 days.…”
Section: Animal Models Of Laryngeal Muscle Exercisementioning
confidence: 96%
“…The extent to which individuals vary with regard to muscle fiber type complement in the intrinsic laryngeal muscles is not currently well understood. 3 It may be that, like limb skeletal muscles, there are individuals who are genetically predisposed to a far larger complement of either Type I or Type II muscle fiber types, providing physiological support for vocal performers we would consider as outliers. Outliers could manifest as either individuals who have little difficulty with extensive use at one extreme or individuals prone to voice disorder at the other extreme.…”
Section: Muscle Fiber Typesmentioning
confidence: 99%
See 1 more Smart Citation